Maresin 1 Improves Cognitive Decline and Ameliorates Inflammation in a Mouse Model of Alzheimer’s Disease - Yin, Ping; Wang, Xu; Wang, Shuang; Wei, Yafen; Feng, Jiachun; Zhu, Mingqin (Frontiers in Cellular Neuroscience, 2019)
Alzheimer’s disease (AD) is one of the most common neurodegenerative disease and accumulating evidences suggest an active role of inflammation in the pathogenesis of AD. Inflammation resolution is an active process that terminates inflammation and facilitates the restoration of inflamed tissue to homeostasis. Resolution of inflammation has been shown to be conducted by a group of specialized pro-resolving lipid mediators (SPMs) including lipoxins, resolvins, protectins, and maresins (MaRs). Recent studies have demonstrated that failure of inflammation resolution can lead to chronic inflammation and, hence, contribute to AD progression. We have previously shown that MaR1 can improve neuronal survival and increase microglial phagocytosis of amyloid-β (Aβ). However, the effects of MaR1 on animal models of AD have not been reported. In this study, we aim to investigate the effects of MaR1 on behavioral deficits and pathological changes in a mouse model of AD. Mice received bilateral injections of Aβ42 protein into the hippocampus, followed by administration of MaR1 by intra-cerebroventricular injection. The behavioral changes in the mice were analyzed using Morris water maze. Immunohistochemistry, Fluoro-Jade B (FJB) staining, cytometric beads array (CBA), and western blot analysis were used to demonstrate molecular changes in the mice hippocampus and cortex. Our results showed that MaR1 treatment significantly improved the cognitive decline, attenuated microglia and astrocyte activation. In addition, we found that MaR1 decreased the pro-inflammatory cytokines TNF-α, IL-6, and MCP-1 production induced by Aβ42 and increased the anti-inflammatory cytokines IL-2, IL-10 secretion with or without Aβ42 stimulation. Moreover, western blot results showed that MaR1 up-regulated the levels of proteins related to survival pathway including PI3K/AKT, ERK and down-regulated the levels of proteins associated with inflammation, autophagy, and apoptosis pathways such as p38, mTOR and caspase 3. To conclude, MaR1 improved the cognitive decline, ameliorated pro-inflammatory glia cells activation via improving survival, enhancing autophagy, inhibiting inflammation and apoptosis pathways. In conclusion, this study shows that inflammation resolution may be a potential therapeutic target for AD.